Minat Belajar dengan Hasil Belajar Biologi - Elijonnahdi Elijonnahdi; Hidayati Suhaili; Titi Sartini; Nurlatifah Nurlatifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the relationship between interest in learning and the biology learning outcomes of class X SMA N 5 Bukittinggi students. This type of research uses correlational. The population in the study were all class X students at SMA N 5 Bukittinggi, totaling 416 people. Sampling used a random sampling technique totaling 70 people. The data in this research is in the form of learning interest and learning outcomes. Data were analyzed using product moment correlation, with a significance level of α = 0.05. The research results show that the results of data analysis obtained for the linearity test are linear with the regression equation y = 1.98 + 0.33x. Analysis of data on interest in learning and learning outcomes shows a correlation coefficient (rcount) = 0.44 and (rtable) = 0.235 (rcount > rtable), which means there is a significant relationship between interest in learning and Biology learning outcomes for class X SMA N 5 Bukittinggi. Meanwhile, the coefficient of determination (r2) = 0.19. In conclusion, interest in learning is related to students' Biology learning outcomes by 19%. Keywords: Biology Learning Results, Interest in Learning